Impact of Weed Infestation on Growth and Yield of Carrot Plants. - Mutabazi, Cosma (Kabale University, 2024)
The study examined the impact of weed infestation on the growth and yield of carrot plants. It was guided by the following study objectives; to determine the effect of weeds on the growth of carrot plants, to identify critical periods of weed competition in carrot plants and to investigate the effect of different weeding regimes on carrot yields. The experiment was carried out at the teaching and research farm of faculty Agriculture, Kabale University Kabale district, Uganda between April 2024 to July 2024. The experiment was carried out in a randomized complete block design (RCBD) within the plot where carrots were planted. The researcher used 5 treatments replicated 3 times. Each experimental plot measured 3m by 1.5 meters in total. The treatments comprised of different weeding regimes as weeding once, weeding twice, weeding thrice, and fourth plus no weeding acting as a control experiment. Primary tillage was the first operation to be done to break up compacted soil, improve aeration, promote better water infiltration, and create a favorable seedbed for optimal carrot growth. Primary tillage is the first soil tillage after the last harvest. On 15th May 2024, two carrot seedlings were sown directly per hole at a spacing of 5cm. These 5 cm were measured using a ruler and holes were dug using a debar. After one week, carrot seeds germinated, and weeding started after two weeks. Data Collection Methods used included observation and measurement. Quantitative data was used during data analysis and it involved the use of frequencies, and tables against their percentages and aided in data interpretation, data analysis, and presentations of findings. The results on all blocks A, B, C, D, and E generally indicated that there overall carrot plant shoot as evidenced by an increase in height, an increase in the number of leaves, and an increase in leaf area. However, there was a limited increase in growth parameters of carrot plants in control block A compared to other blocks. The above results generally indicated that marketable carrot root tubers were high compared to unmarketable ones simply because the blocks that were weeded experienced a weed-free environment which made carrot crops grow well and give high yields. The study also recommended Implementing integrated weed management practices that combine cultural, mechanical, and chemical methods. For instance, using cover crops or mulching can suppress weed growth while promoting carrot health.